Kansas higher education policies and the impact on college access: a critical policy analysis - Pfeifer, Justin David (Kansas State University, 2023)
The purpose of this mixed-methods study is to examine the power differentials that manifest within Kansas public higher education due to policies surrounding territory assignments and degree offerings for Kansas two-year community and technical colleges. The study provides insight into the differential effects of these policies among different populations on access to higher education, based on their geography. Using critical policy analysis, the study explored the policy language, the political forces at work, and the impact the policy has on access to higher education in the state of Kansas. Specifically, the study included analysis of legislation, policy documents, documentation of funding structures, and federal financial aid policies and guidance. The analysis utilized spatial inequality as a theoretical framework to compare college attainment rates across geographical areas. Geographic comparison is especially relevant in this study due to policies that impact populations differently based on the county where they reside. In this study, attention is given to the extent discourse of these policies influence college going behaviors, particularly for traditionally underserved populations such as low income, minority, and firstgeneration students. Results from the qualitative phase found a contradiction between the goal of Kansas policymakers to increase higher education attainment and their goal to reduce duplication in academic programming, which limits opportunities and access for broad geographic areas of the state. The quantitative phase identified spatial disparities in access to the different higher education sectors across the state, including the identification of education deserts and match deserts. The results of this study provide insights and recommendations for policymakers to address unnecessary barriers and increase college accessibility for all Kansans.
Keywords: College access; Kansas; Geography; Spatial inequality; Critical policy analysis